Transverse momentum dependent distribution functions in the threshold limit - Zhong-Bo Kang; Kajal Samanta; Ding Yu Shao; Yang-Li Zeng (Journal of High Energy Physics, 2023)
Abstract We apply the joint threshold and transverse momentum dependent (TMD) factorization theorem to introduce new threshold-TMD distribution functions, including threshold-TMD parton distribution functions (PDFs) and fragmentation functions (FFs). We apply Soft-Collinear Effective Theory and renormalization group methods to carry out QCD evolution for both threshold-TMD PDFs and FFs. We show the universality of threshold-TMD functions among three standard processes, i.e. the Drell-Yan production in pp collisions, semi-inclusive deep-inelastic scattering and back-to-back two hadron production in e + e − collisions. In the end, we present the numerical predictions for different threshold-TMD functions and also transverse momentum distributions at pp, ep, and e + e − collisions.